Reference intervals for absolute and percentage immature platelet fraction using the Sysmex XN-10 automated haematology analyser in a UK population. (17th November 2017) - Ali, Usman; Knight, Gavin; Gibbs, Roz; Tsitsikas, Dimitris A.
Abstract: Background: Immature platelet fraction (IPF) estimation is a non-invasive and sensitive test that is available on recently introduced Sysmex XN-series of automated haematology analysers. It is a direct cellular indicator of thrombopoiesis. The aim of this study was to establish reference intervals for IPF, for both absolute (A-IPF) and percentage (%-IPF) measurements. Material and methods: A total of 2366 samples that met the inclusion criteria were assayed for full blood count on the Sysmex XN-10 and a non-parametric percentile method was used for calculating the reference intervals. Results: After the outliers were excluded, the reference interval for %-IPF and A-IPF on Sysmex XN-10 were 1.6–10.1% and 4.37–23.21 × 10 9 /L in total individuals, respectively. There was a statistical significance noted between the sexes ( p = .004) for %-IPF, therefore a sex-specific reference interval was established, which was 1.8–10.0% for the males and 1.5–10.1% for females. No significant difference in sex status for A-IPF and age status for both %-IPF and A-IPF was observed. A very poor correlation was estimated between age versus %-IPF, ρ = 0.0156, and age versus A-IPF, ρ = −0.0023, indicating that there is no overall biological relationship between age and these parameters. As expected, a strong correlation between %-IPF and A-IPF was noted which could be attributed to their inter-relatedness. Conclusions: This large-scale study showed comparable reference intervals with the previous studies for %-IPF and A-IPF in a UK population. It found the need to establish sex-specific reference intervals for %-IPF, but not for A-IPF, whereas reference intervals were found to be stable across the age range.